National symbols in modern Iran : identity, ethnicity, and collective memory - Merhavy, Menahem (Modern intellectual and political history of the Middle East., 2019)
"Examining the ways in which Iranians have argued, debated, and struggled over national symbols throughout the last four decades, Merhavy focuses on national symbols such as Cyrus the Great and Persepolis and the ways in which they have been interpreted by Iranian publicists, government officials, and religious leaders. He examines continuity versus change triggered by the revolution of 1979, which culminated in the establishment of the Islamic Republic, and demonstrates the limited nature of the state's ability to influence society on a broad level. Merhavy shows how religious, cultural, and social institutions are influenced by, and influence in turn, the processes of modernization in contemporary Iran and, ultimately, suggests that we must rethink some of our basic assumptions about the dominant role the modern nation-state plays in shaping society"--